Effective Training and Employee Performance in a Firm, A Case Study of C-Care Imc (International Medical Center) Kireka. - Shadrach Nyende (Uganda Christian University, 2023)
ABSTRACT This study was carried out to assess “The impact of effective training and employee performance in a firm” , a case study of C-care IMC (International Medical Center ), Kireka. The objectives of the study were; To examine the relationship between proper planning for training and employee performance in a firm, to examine the relationship between use of effective instructional/ training media and employee performance in a firm and lastly to examine the relationship between transfer of knowledge/ feedback on training and employee performance in a firm. The study population was 60 employees of C-care International Medical Center, Kireka and the sample size of 52 was selected. A quantitative research design and a cross-sectional survey design was used to collect and analyze data. The study used self-administered structured questionnaires, a principle data collection instrument, which were administered to the staff of C-care IMC Kireka. Respondents in the selected population were stratified inorder to respond to the questionnaires. The analysis of the collected data was done by use of descriptive statistics in the form of frequency tables and means aided by the statistical package for social sciences. Findings revealed that, for attainment of effective training, managers ought to consider three major aspects in their programs which include; Firstly, ensuring proper planning for training, which must cover clear communication of training objectives to the trainees but as well endeavor to provide all necessary resources for these programs to be executed successfully. Secondly, it’s the use effective instructional media for example multimedia presentations, videos, or interactive content that will ensure trainee’s engagement and participation in the training and lastly also ensure that there is ability to transfer knowledge from the training programs by providing constructive feedback on the performance of their employees after these programs but most importantly providing ample opportunities to the trainees to practice what they have learnt on their real job roles in the organization. The study recommends that there be an investigation on the impact of tailoring training programs to individual employee needs and job roles. Future researchers should extend the research to different industries and sectors to determine whether the impact of effective training on firm performance varies across industries. This could provide valuable insights into industry-specific training needs and strategies.
This is a dissertation.